Analisis pelaksanaan asesmen portofolio di kelas V sekolah dasar - Nisa Apriliani Apriliani; Ghullam Hamdu; Agnestasia Ramadhani Putri (IKIP Siliwangi, 2024)
The purpose of this research is to reveal and describe the implementation of portfolio assessments carried out by teachers in the learning process. Based on the literature review, this research is motivated by the suboptimal implementation of portfolio assessment. This study was conducted at SD Negeri Indihiang, with VC class teachers as participants. The study utilized a descriptive analysis method with a qualitative approach. Data were collected using interview guidelines and documentation. The study’s findings revealed several steps in compiling portfolio assessments that were not carried out: (1) the teachers did not hold regular meetings to reflect on student performance results. This is due to the teacher's difficulties in managing time to meet the demands of learning objectives; (2) the teachers did not provide continuous feedback on student work, as there was no because selection process based on criteria; and (3) during the assessment stage, the teacher still does not use the scoring rubric, thereby unable to enforce the assessment criteria on performance results. This is due to the teachers inability to develop an assessment rubric.